Acinetobacter baumannii: challenges presented by a drug-resistant pathogen - Goncalves, E.K.; Ramos, L.A.; Seibert, A.; Ribeiro, L.M.; McDuffie, S.L.; Murray, M.C.; Fiester, S.E. (Frontiers in Bacteriology, 2026)
Acinetobacter baumannii has emerged as a significant bacterial pathogen with the ability to cause recalcitrant and often deadly systemic infections due to the proclivity of encountering drug-resistant isolates clinically and this pathogen’s ability to evade immune responses while causing significant pro-inflammatory reactions during infection. Novel therapies to combat resistant isolates have shown promise but variable efficacy in clinical trials. Research efforts to expand the pathophysiological understanding of this bacterium for the ultimate identification of new therapeutic targets for use in the development of novel therapeutics are limited by strain heterogeneity and inconsistent preclinical models. This perspective highlights clinical challenges experienced in treating these infections, potential strategies that could be utilized in the research and development of effective therapies and clinical management of A. baumannii infection.